Distribuição e diversidade espaço- temporal da Classe Collembola na região central do Rio Grande do Sul, Brasil - Coghetto, Franciele (2015)
As long as the agricultural expansion progresses over the Pampa biome, the simplification and contamination of environments have become the main causing agents of loses of diversity of several soil organisms, among them the springtails. The Collembola class is one of the most plentiful groups present in the soil fauna; being responsible for the fragmentation of plant detritus, fungi dispersion, decomposition, nutrient mineralization and others; developing this way an elementary function at the dynamic of ecosystem operation. Springtails have a cosmopolitan distribution and can be found in almost all ecosystems, from the flooded areas until the higher elevations. Besides performing fundamental role at the ecosystem operation and be present in all zoogeographic regions, studies about Collembola class are overlooked and incipient at many areas, which is the case of Rio Grande do Sul. To that end, this study had as objective to schedule the distribution of springtails in different soil uses at the Central Depression Area of Rio Grande do Sul, allying taxonomic study to ecological parameters, aiming to contribute for the knowledge about dynamics of Collembola population in different soil uses at this region. Collects were performed with the aid of PROVID traps between November of 2013 and June of 2014, covering the annual seasonality. At all, were identified nineteen species and eighteen genders belonging to seven different families. The results showed indications of seasonality on the springtails distribution, and a preference for protected forest area, with eleven species belonging to six families collected. The area with less richness of species was the impacted one, with seven species belonging to four families, and the tillage with eight species belonging to four families collected. These data suggest to the loses of diversity caused, mainly, by ecosystem fragmentation and indiscriminate use of agrochemicals.